Control interno contable del período 2022 en el Gobierno Autónomo Descentralizado Rural de la parroquia Ricaurte. - Monserrate Pisco, Luzmila Cecibel (2024)
The case study of the Rural Decentralized Autonomous Government of the Ricaurte parish for the period 2022 addresses the essence of accounting and auditing, focusing on internal accounting control as a fundamental pillar for the transparency and effectiveness of financial management. The research arises from the need to evaluate the robustness of the internal accounting control system, identify the level of confidence in said system and verify the execution of internal control through surplus/deficit analysis, emphasizing the importance of responsible and transparent public management. . This study not only seeks to expose existing gaps but also propose practical improvements that contribute to the sustainable development of the community. The methodology adopted to carry out this research combined the documentary analysis of the GAD's financial information with the application of an internal control matrix structured around the five phases of internal control, allowing a comprehensive evaluation of the accounting processes. Through this approach, it was possible to capture a reliable image of the GAD's financial situation, evaluating the effectiveness of its internal controls and its ability to efficiently manage public resources.